Silicone membranes to inhibit water uptake into thermoset polyurethane shape‐memory polymer conductive composites. Issue 1 (24th July 2014) - Yu, Ya‐Jen; Infanger, Stephen; Grunlan, Melissa A.; Maitland, Duncan J.
ABSTRACT Electroactive shape memory polymer (SMP) composites capable of shape actuation via resistive heating are of interest for various biomedical applications. However, water uptake into SMPs will produce a depression of the glass transition temperature (Tg) resulting in shape recovery in vivo. While water actuated shape recovery may be useful, it is foreseen to be undesirable during early periods of surgical placement into the body. Silicone membranes have been previously reported to prevent release of conductive filler from an electroactive polymer composite in vivo. In this study, a silicone membrane was used to inhibit water uptake into a thermoset SMP composite containing conductive filler. Thermoset polyurethane SMPs were loaded with either 5 wt % carbon black or 5 wt % carbon nanotubes, and subsequently coated with either an Al2O3‐ or silica‐filled silicone membrane. It was observed that the silicone membranes, particularly the silica‐filled membrane, reduced the rate of water absorption (37°C) and subsequent Tg depression versus uncoated composites. In turn, this led to a reduction in the rate of recovery of the permanent shape when exposed to water at 37°C. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41226.